(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper contains the presentation at the commemoration of the 100th Anniversary of the Birth of Acad. Alexandru Timotin at the Romanian Academy on April 29, 2025. Some of his outstanding scientific contributions are described. The appendix shows the relevance of his discoveries.